1999
DOI: 10.1007/s004380050925
|View full text |Cite
|
Sign up to set email alerts
|

The S / M checkpoint at 37°C and the recovery of viability of the mutant polδts3 require the crb2 + /rhp9 + gene in fission yeast

Abstract: We have isolated a mutant in fission yeast, in which mitosis is uncoupled from completion of DNA replication when DNA synthesis is impaired by a thermosensitive mutation in the gene encoding the catalytic subunit of DNA polymerase delta. By functional complementation, we cloned the wild-type gene and identified it as the recently cloned checkpoint gene crb2+/rhp9+. This gene has been implicated in the DNA damage checkpoint and acts in the Chk1 pathway. Unlike the deleted strain dcrb2, cells bearing the crb2-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 42 publications
4
16
0
Order By: Relevance
“…We also found that wild-type cells recover from HU treatment more quickly at 36°C with increased RPA foci. This is consistent with previous studies in fission yeast that indicate checkpoints are temperature sensitive (16,21).…”
Section: Discussionsupporting
confidence: 93%
“…We also found that wild-type cells recover from HU treatment more quickly at 36°C with increased RPA foci. This is consistent with previous studies in fission yeast that indicate checkpoints are temperature sensitive (16,21).…”
Section: Discussionsupporting
confidence: 93%
“…Earlier studies showed that Crb2/Rhp9 functions upstream from and interacts physically with Chk1 and that Crb2/Rhp9 is required for checkpoint integrity and maintenance of viability after swi7/pol1, cdc6/pol␦, or cdc20 ts mutants are shifted to the restrictive temperature (21,38). The decline in viability and the FIG.…”
Section: Resultsmentioning
confidence: 95%
“…In fission yeast these include the "checkpoint Rad" proteins Rad1, Rad3, Rad9, Rad17, Rad26, and Hus1, which are also required for cell cycle arrest following DNA damage (1,2,14,37). Components involved in checkpoint signalling following HU treatment differ subtly from those involved following DNA polymerase inhibition, with Crb2/Rhp9 being required for the latter but not the former (21,38,45). The Cds1 protein kinase functions downstream from the checkpoint Rad proteins to promote cell survival after both forms of S-phase inhibition (34).…”
mentioning
confidence: 99%
“…crb2 null mutants lack checkpoint induced arrests in response to UV, gamma-irradiation and MMS and fail to grow in the presence of HU (hydroxyurea), a defect unrelated to the DNA damage checkpoint function but reflective of a problem in recovery (Saka et al . 1997;Grenon et al . 1999).…”
Section: /Rad4mentioning
confidence: 99%
“…1997; Saka et al 1997;Grenon et al 1999). Here we report the isolation of rhp51 + as a multicopy suppressor of the conditional MMS sensitivity of mutant crb2-1 and the characterization of genetic interactions between rhp51 + and crb2 + and other checkpoint genes.…”
Section: Figurementioning
confidence: 99%